Elemental abundance studies of CP stars. The helium-weak stars HD 19400, HD 34797 and HD 35456 - Alonso, M.S. (2003)
An analysis of the abundances of the helium-weak CP stars HD 19400, HD 34797 and HD 35456, is presented using ATLAS9 model atmospheres and observational material taken with a REOSC echelle spectrograph attached to the Jorge Sahade 2.15 m telescope at CASLEO. The light elements are deficient except silicon which is overabundant in HD 19400 and HD 34797. The iron peak elements are all overabundant by factors between 5 and 60. The heavy elements show an overabundance in the three stars studied.